Feeding strategies of domestic animals from the settlement of Leceia (Oeiras, Portugal) during the transition from the 4th to the 3rd millennium BC: stable isotope approach: DOI: 10.5281/zenodo.12732048 - Navarrete, Vanessa (2024)
In this article, we analyse faunal samples from the Late Neolithic (Layer 4) and Early Chalcolithic (Layer 3) levels of the fortified settlement of Leceia (Oeiras, Portugal) in order to understand the management of the feeding of domestic animals recovered in these excavations. Through the analyses of stable isotopes of δ13C and δ15N in bone collagen, we aim to characterise the grazing systems and the maintenance strategies of the livestock that were consumed and raised in Leceia, in an attempt to obtain a further perspective on the economic complexity of the fortified settlements that emerged during the 3rd millennium in Portuguese Extremadura. The results show the possible use of forage to feed the animals and also seem to indicate the use of fertilised fields. This demonstrates that animal production is already based on intentional practices of animal and land management, as well as on complex exchange networks.